Students' Use Of Formal And Informal Knowledge About Energy And The Human Body - Mann, Michael Frank (Curtin University, 2003)
During the past three decades, much research has occurred into students' conceptions as well as factors influencing them and how the conceptions are formed. This study reports on students' conceptions involving energy and the human body. Initially, a number of student conceptions within the overarching area of energy and the human body were identified by developing and administering questionnaires to 610 students ranging from Year 8 through to Year 12. Students' responses to the questionnaire items resulted in previously identified conceptions as well as a number of unreported ones. The unreported notions included: carbohydrates are different to sugars; energy is needed for organs to function; fats and their role in energy storage; the eye and ear do not convert energy but transfer it to the brain; sweat cools the skin due to contact with air; objects need energy to start moving but not to move; and aspects of respiration and digestion. Conceptions such as the particulate nature of energy, energy's usefulness, conservation and transfer of energy, role of digestion and respiration, sources of energy were associated with previously identified notions which were derived from both informal and formal learning situations. But, it was not possible to distinguish which source knowledge was derived from. From these notions, a series of possible pathways for conceptual development within the area of energy and the human body were described. Further analysis of the data indicated a number of ontological changes that can occur as the student-cohort became older. These ontological changes included a decline in the notion of energy being particulate to being non-particulate and not being described, through to being involved in the chemical bonds of molecules, the role and processes of digestion, the number of energy types and energy sources and how the eye and ear function.All these conceptions changed with student age and became more scientifically acceptable in their nature as students' formal education increased. Based upon the findings of the above questionnaires, a diagnostic paper and pencil instrument set of 20 items based upon a modified two tier multiple-choice format was developed to identify student held conceptions on energy and the human body. Subsequently, an interventionist strategy was designed and implemented to help students avoid the development of misconceptions as they construct acceptable concepts related to digestion and to respiration. This strategy follows the passage of food from its ingestion through to the absorbed foods conversion into ATP for use by the body. The findings of this study are to be of use to science teachers worldwide, not only in Western Australia as the findings of this thesis are relevant to educators of students in Years 8 to 12. The findings are related to energy in general but specifically to the students' own body. These findings relate directly to an intrinsically interesting feature, the student's own body. Another outcome of these misconception findings are two instruments which are likely to be of value to educators of Years 8 to 12 students. These are a diagnostic instrument designed to identify a number of alternative conceptions learners may hold and secondly a lesson sequence dealing with digestion and respiration and the role these have in the conversion and transfer of energy in the body.